2017
DOI: 10.5370/jeet.2017.12.2.865
|View full text |Cite
|
Sign up to set email alerts
|

Copper Particle Effect on the Breakdown Strength of Insulating Oil at Combined AC and DC Voltage

Abstract: -Converter transformer is the key equipment of high voltage direct current transmission system. The solid suspending particles originating from the process of installation and operation of converter transformer have significant influence on the insulation performance of transformer oil, especially in presence of DC component in applied voltage. Under high electric field, the particles easily lead to partial discharge and breakdown of insulating oil. This paper investigated copper particle effect on the breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…In recent years, the research about conductive particles bridging was mainly executed by Wang et al [76,77]. According to their experimental results, the dependence of bridge formation on voltage types was analogous to the case with cellulose particles, as shown in Fig.…”
Section: Formation Of Particle Bridgementioning
confidence: 98%
“…In recent years, the research about conductive particles bridging was mainly executed by Wang et al [76,77]. According to their experimental results, the dependence of bridge formation on voltage types was analogous to the case with cellulose particles, as shown in Fig.…”
Section: Formation Of Particle Bridgementioning
confidence: 98%
“…Its mathematical expression is shown by Equation (22), where t stands for the DC breakdown strength; α stands for the scale parameter, which describes the characteristic breakdown strength of oil; and β represents the shape parameter, which reflects the changing rate of breakdown probability with an increase in DC voltage. The data samples used in this study were complete, so the empirical distribution function F n (t i ) could be calculated by Formula (23), where i represents the order of test samples, and n is the number of samples. Figure 6 is the Weibull probability distribution plot of different samples under the DC breakdown voltage.…”
Section: Effect Of Particles Accumulation On Oil DC Breakdown Voltagementioning
confidence: 99%
“…In [21,22], the motion trajectory of a metal particle in flowing oil under AC voltage was provided. The movement process of a millimeter-diameter metal particle between electrodes has been investigated under various forms of voltage, and it has been stated that the voltage form and particle concentration have important impacts on the motion characteristics of metal particles [23,24]. The movement properties of millimeter-diameter metal particles under AC voltage have been investigated by numerous researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Sarathi et al [7, 8] found that the PD frequency at AC voltages was higher than that at direct current (DC) voltages because of the more intense particle movement in AC electric fields. Besides, Wang et al [9] concluded that the increase of the collisions between particles and electrodes induced more PDs as the DC component increased at composite AC and DC voltages, which reduced the breakdown voltage of insulating oil.…”
Section: Introductionmentioning
confidence: 99%